Observation of Brillouin linewidth broadening and decay time in photonic crystal fiber - Stiller, Birgit; Beugnot, J. C.; Foaleng Mafang, S.; Lee, M. W.; Delqué, M.; Kudlinski, A.; Maillotte, H.; Laude, V.; Thévenaz, L.; Sylvestre, T. (2010 IEEE Photonics Society Summer Topical Meeting Series, PHOSST 2010, 2010)
We present a novel distributed sensing technique that allows for the observation of Brillouin gain spectral distribution and acoustic decay time in photonic crystal fiber as well as in standard single-mode fiber. © 2010 IEEE.
CRIS-Team Scopus Importer:2021-06-29